SENSORY QUALITY OF DRIED NOODLES MADE WITH THE ADDITION OF FRESH MUSSEL MEAT (pilsbryoconcha sp.) DIFFERENT TREATMENT - Giffar Ali Firmansyah; Bustari Hasan; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract       This study aims to evaluate the sensory qualities of dried noodles of freshwater mussel (kijing) made from fresh meat, boiled meat and a mixture of fresh and boiled meat. The research method used is an experimental, namely the processing of dried mussel noodles made with the addition of mussel meat with different treatments. The design used was a one-factor Completely Randomized Design (CRD), with 4 levels, namely: without the addition of mussel meat (Mo), the addition of 100 g of fresh mussel meat (M1), the addition of 100 g of boiled mussel meat (M2), and the addition of mixed meat (50 g fresh meat and 50 g boiled meat) (M3). Based on the research, the addition of mussel meat can increase the appearance value of mussel dried noodles but has no effect on the aroma, taste and texture of the mussel noodle produced. The value of appearance, aroma, taste and texture of kijing dried noodles was not significantly different between those made from fresh meat, boiled and a mixture of fresh and boiled meat. Dried noodle of kijing made with the addition of boiled meat (M2) was most preferred by consumer acceptance. However was not different among treatment.Keywords: mussel, mussel dried noodle, sensory quality